Plasticity in the shape and growth pattern of asteriscus otolith of black prochilodus Prochilodus nigricans (Teleostei: Characiformes: Prochilodontidae) freshwater Neotropical migratory fish - Rosa Maria Rodrigues da Costa; Nidia Noemí Fabré; Sidinéia Aparecida Amadio; Víctor Manuel Tuset (Neotropical Ichthyology, 2018)
ABSTRACT Using morphometric measurements and wavelets functions, the asterisci otoliths of curimatã, Prochilodus nigricans were analysed to identify the variation in shape and growth increment of individuals from Solimões, Japurá and Negro rivers of the Amazon basin, Brazil. The morphometric and morphological analyses did not reveal evidences of population segregation among rivers, but variations were found in the estimation of otolith growth increment. Also, the otolith shape showed a high variability between individuals, identifying four morphotypes. Morphotype 1 shows a more oval shape with a posterior zone clearly rounded; Morphotype 2 shows the posterior zone rounded, but the anterior end is more elongated; Morphotype 3 shows a completely different shape, elliptic-pentagonal and Morphotype 4 shows the posterior zone rounded, but the anterior end is more elongated and it is the pattern with antirostrum and rostrum more pointed and a deep notch. Therefore, the otolith shape exhibited a phenotypic plasticity that it was not associated with the metabolism of otolith growth. Whereas the otolith shape indicated a homogeneity in the sound perception through Amazon basin, the growth rates revealed an adaptive mechanism to environmental conditions or migratory process of this species.